Research of Efficiency of Security System Sensors - Bagdanavičius, N.; Besakirskas, A.; Eidukas, D.; Janulis, M. (Elektronika ir Elektrotechnika, 2003)
It was shown, that in order to value the efficiency of electronic security system (ESS), you have to know efficiencies of its components. In order to instance evaluation possibilities of efficiency of individual ESS pieces, several calculation methods of efficiency of sensors (of sensors, as individual electronic devices, of sensors definable with many indexes and sensors, used by security of territory perimeter) were presented. It was shown, how is efficiency of security changing, by using several sensors for the same area secure and by evaluation chances of incorruptibility of these sensors. Ill. 7, bibl. 4 (in Lithuanian; summaries in Lithuanian, Russian, English).